ACTION AGAINST NEW DRUG TYPE GORILLA TOBACCO AT WONOSOBO POLICE REGENCY - Ichsanudin, Ichsanudin; Gunarto, Gunarto (UNISSULA Semarang, 2023)
This research aims to determine the implementation of the enforcing process againts the new drug types of tobacco gorilla in Wonosobo Police Resort based on the Criminal Code (KUHAP). This research is a descriptive empirical law research, by doing research on the implementation of the action on the new drug tobacco gorilla in Police Resort Wonosobo. The type of data used is primary data and secondary data. Secondary data sources include primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques used are literature studies, in the form of books, and documents and field studies. Data analysis technique use interactive model of analisys, that is process analyze by using three component, that is data collecting, data reduction, and conclusion. Based on the discussion resulted the conclusion, first is the implementation of the action against the new drug type of tobacco gorilla in Wonosobo Police Resort has been done properly according to the law in Indonesia. Secondly, obstacles experienced in the process of action against new types of drugs gorilla tobacco in Wonosobo Police ResortKeywords: Action, Gorilla Tobacco